Ankyloblephron Filiform Adnatum: A Case Report - Jain, Divya; Bandyopadhyay, Tapas; Tomar, Vasudha; Rai, Ruch (Nepalese Journal of Ophthalmology, 2019)
Ankyloblephron filiform adnatum (AFA) is a rare benign congenital anomaly that can arise either in isolation or associated with a syndrome. It should be treated as early as possible due to its ambylogenic potential. We report a case of a successfully managed newborn that had sporadic AFA detected at birth. Our case is unique in the sense that sporadic AFA with Atrial septal defect has not been reported in the literature.